The EU's tacit yet unspoken attitude towards Turkey's EU accession process: viewing Turkey as 'a European outsider' - Hakan Samur; Turgut Demirtepe (Eastern Journal of European Studies)
Turkey's accession process to the European Union has been a prolonged journey. The objective of this article is to scrutinize the role of the European Union in extending this process. A thorough analysis of the relations between Turkey and the EU from the 1960s to the present demonstrates a notable discrepancy between the EU's official rhetoric and its tangible actions concerning Turkey's membership. In official statements, the EU has consistently underscored Turkey's Europeanness and its suitability for membership. However, an examination of the EU's attitude reveals a stark contrast to these declarations, suggesting that the EU's commitment to Turkey's membership is superficial at best. It is frequently asserted by the EU that Turkey suffers from significant shortcomings in meeting the economic, political, and institutional criteria required for membership, which are often cited as key obstacles to accession. However, even during periods when Turkey has made genuine and determined efforts to address these deficiencies, the EU's stance has largely been characterized by institutional inertia and lack of genuine engagement. Moreover, the constructive approach extended to other candidate countries has conspicuously not been applied to Turkey. Similarly, since the 1990s, reluctance toward Turkey's accession has been openly articulated by certain EU officials. Through a qualitative and diachronic analysis of key events and official statements, this study aims to illustrate all these points with concrete examples and to argue that the primary impediment to Turkey's EU membership lies not in the country's shortcomings, but rather in the EU's principled and persistent opposition to Turkish accession.